Korean Wave and Sharing Idol Goods in Indonesia - Adi Teguh Suprapto; Agung Sudjatmoko; Meiny Meiny; Verren Veronica; Regita Cynthia Wijaya (Journal of Innovation in Business and Economics, 2025)
This study examined the impact of the Korean wave, brand ambassadors, and sharing idol goods on purchase intention within the autobase@dagangkorea Twitter community. Analyzing data from 100 respondents through a quantitative research approach, the findings indicate that the Korean wave alone did not significantly influence purchase intention. However, brand ambassadors and the sharing of idol goods both demonstrated positive and significant effects on purchase intention. Notably, when considered together, these factors collectively exerted a positive and significant influence on purchase intention. This suggests that, in this specific Twitter community, brand ambassadors and the exchange of idol goods are crucial in shaping purchase decisions, while the broader cultural influence of the Korean wave may not directly impact buying choices.